Single and Twofold Metal‐ and Reagent‐Free Anodic C−C Cross‐Coupling of Phenols with Thiophenes. Issue 46 (20th October 2017) - Wiebe, Anton; Lips, Sebastian; Schollmeyer, Dieter; Franke, Robert; Waldvogel, Siegfried R.
Abstract: The first electrochemical dehydrogenative C−C cross‐coupling of thiophenes with phenols has been realized. This sustainable and very simple to perform anodic coupling reaction enables access to two classes of compounds of significant interest. The scope for electrochemical C−H‐activating cross‐coupling reactions was expanded to sulfur heterocycles. Previously, only various benzoid aromatic systems could be converted, while the application of heterocycles was not successful in the electrochemical C−H‐activating cross‐coupling reaction. Here, reagent‐ and metal‐free reaction conditions offer a sustainable electrochemical pathway that provides an attractive synthetic method to a broad variety of bi‐ and terarylic products based on thiophenes and phenols. This method is easy to conduct in an undivided cell, is scalable, and is inherently safe. The resulting products offer applications in electronic materials or as [OSO] 2− pincer‐type ligands. Abstract : First into the congested vicinity of sulfur and then to the other side—these are the positions wherein the dehydrogenative arylation reaction occurs. This allows thiophenes to be easily equipped with hydroxyphenyl moieties in a very simple to perform and scalable procedure from common precursors.